Feature of the spatial position of the spine in pole vaulters - Gapicheva, M.; Pletnev, A.; Ushakov, A. (Human. Sport. Medicine, 2020)
The study aims to analyze the spatial position of the spine in pole vaulters. Materials and Methods. Pole vaulters participated in the study. Ten male jumpers ages 16-23 from the second adult category to the master of sports of international class were examined. The spatial position of the spine was recorded by using the MBN 3D scanner system. Six indicators were analyzed that clearly reflect the position of the vertebral column in relation to the sagittal and frontal planes. Results. Statistically significant changes were found in three of the six projection angles relative to the sagittal and frontal planes, namely the angles: L-3D-X - the relative position of the lumbar spine (Th12-L5) and sagittal plane (degrees), 3D Y - the relative position of the cervical spine (C2-C7) and frontal plane (degrees), and L-3D-Y - the relative position of the lumbar spine (Th12-L5) and frontal plane (degrees). Conclusion. The analysis of the spatial position of the spine in pole vaulters showed signs of sports adaptation in jumpers. As a result, there is a forward tilt of the projection of the cervical spine, as well as a forward tilt of the projection of the lumbar spine and a rotation of the pelvis to the right in the sagittal plane. Asymmetry was recorded at each stage of sports training course from sports specialization to performance enhancement.